2019
DOI: 10.1155/2019/5430904
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Catalytic Activity and Surface Properties of Manganese-Zinc Ferrite Prepared from Used Batteries

Abstract: The catalytic activity of the Mn-Zn ferrites obtained by chemical methods from a solution after acid leaching of waste Zn-C and Zn-Mn batteries was studied. Precursors of metal ions (Fe, Mn, and Zn) were obtained using different precipitating agents ((NH4)2C2O4, Na2CO3, and NaOH), and then, the combustion route was used to prepare catalytically active nanocrystalline ferrites. The obtained ferrite catalysts differ in terms of microstructure, the number of acid and base sites, and the surface composition depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 48 publications
(60 reference statements)
0
6
0
Order By: Relevance
“…presence of co-ordinatively unsaturated metal centres are responsible for the Lewis acidic character of such perovskite structured materials. [111] As can be seen from Scheme 3, the desired product was formed as a result of the intermolecular mannich reaction between β-enaminone and imine (formed by the combination of amine and β-ketoester & aldehyde and amine respectively). The in-situ developed intermediate further reacts with the remaining one molecule of aldehyde to generate another intermediate which further tautomerized and subsequently undergoes intramolecular mannich reaction to deliver the required product.…”
Section: Mechanistic Evaluationmentioning
confidence: 99%
“…presence of co-ordinatively unsaturated metal centres are responsible for the Lewis acidic character of such perovskite structured materials. [111] As can be seen from Scheme 3, the desired product was formed as a result of the intermolecular mannich reaction between β-enaminone and imine (formed by the combination of amine and β-ketoester & aldehyde and amine respectively). The in-situ developed intermediate further reacts with the remaining one molecule of aldehyde to generate another intermediate which further tautomerized and subsequently undergoes intramolecular mannich reaction to deliver the required product.…”
Section: Mechanistic Evaluationmentioning
confidence: 99%
“…e procedure continues with several reactions after the production of teff straw ash. Because sodium silicate, also known as water glass, is the precursor for the sol-gel process, the step after heat breakdown was the synthesis of sodium silicate solution [27]. e process continues with the reactions of recovery, hydrolysis, and condensation.…”
Section: Reaction Mechanismmentioning
confidence: 99%
“…SEM is widely used for it but TEM is better than SEM because of poor resolution of SEM. AFM is a technique that can be used in different conditions like air, vacuum, liquid and moist conditions.Winiarska et al [205] observed that the TEM gave core shell type structure formation.Mirsekari et al [204] found from the SEM micrographs that the morphology of MnZn ferrite was porous, sponge like and agglomerated with an average particle size of 2µm. Anwar et al [9] observed from the SEM micrographs that the particles were spherical in shape.Gabal et al [206] studies showed that TEM morphology showed very strong agglomeration of the cubic particles, having some particles in one line.…”
Section: Morphological Structurementioning
confidence: 99%